Excretion of cytoplasmic proteins (ECP) in Staphylococcus aureus. Issue 4 (19th June 2015) - Ebner, Patrick; Prax, Marcel; Nega, Mulugeta; Koch, Iris; Dube, Linda; Yu, Wenqi; Rinker, Janina; Popella, Peter; Flötenmeyer, Matthias; Götz, Friedrich
Summary Excretion of cytoplasmic proteins (ECP) is a common physiological feature in bacteria and eukaryotes. However, how these proteins without a typical signal peptide are excreted in bacteria is poorly understood. We studied the excretion pattern of cytoplasmic proteins using two glycolytic model enzymes, aldolase and enolase, and show that their excretion takes place mainly during the exponential growth phase in Staphylococcus aureus very similar to that of Sbi, an IgG‐binding protein, which is secreted via the Sec‐pathway. The amount of excreted enolase is substantial and is comparable with that of Sbi. For localization of the exit site, we fused aldolase and enolase with the peptidoglycan‐binding motif, LysM, to trap the enzymes at the cell wall. With both immune fluorescence labeling and immunogold localization on electron microscopic thin sections aldolase and enolase were found apart from the cytoplasmic area particularly in the cross wall and at the septal cleft of dividing cells, whereas the non‐excreted Ndh2, a soluble NADH:quinone oxidoreductase, is only seen attached to the inner side of the cytoplasmic membrane. The selectivity, the timing and the localization suggest that ECP is not a result of unspecific cell lysis but is mediated by an as yet unknown mechanism.